PERAN ENTREPRENEURIAL ORIENTATION TERHADAP KINERJA PERUSAHAAN MELALUI TOTAL QUALITY MANAGEMENT (STUDI DI PERUSAHAAN MEBEL PT KAYAN JAYA TANJUNG) - Timotius FCW Sutrisno; Gladys G Gosal; Richard Surya (School of Business, Bogor Agricultural University (SB-IPB), 2021)
The application of the concept of Total Quality Management (TQM) is expected to be able to assist companies in responding to consumer needs in the future. This research aims to see the mediating effect of Total Quality Management on Entrepreneurial Orientation with Firm Performance. To support this theory, this study takes data from the furniture company PT Kayan Jaya Tanjung, Surabaya. This study was analyzed using the partial least square method by using 78 workers at PT Kayan Jaya Tanjung with a minimum level of manager. Respondents were drawn based on two branch factories, namely PT Kayan Jaya Tanjung I and PT Kayan Jaya Tanjung II. The results of this study indicate that the company can gather its human resources (TQM) to formulate a proactive strategy to anticipate future customer demand (EO) so that companies can maintain the quality of their products (firm performance). This study shows that applying the concept of TQM with a good entrepreneurial orientation will form a sustainable strategy to achieve a competitive advantage for company performance. Keywords: competitive advantage, entrepreneurial orientation, furniture, total quality management, firm performance